Prevalent Class I-Restricted T-Cell Response to the Theiler’s Virus Epitope D(b):VP2(121–130) in the Absence of Endogenous CD4 Help, Tumor Necrosis Factor Alpha, Gamma Interferon, Perforin, or Costimulation through CD28 - Johnson, Aaron J. (American Society for Microbiology, 1999)
C57BL/6 mice mount a cytotoxic T-lymphocyte (CTL) response against the Daniel’s strain of Theiler’s murine encephalomyelitis virus (TMEV) 7 days after infection and do not develop persistent infection or the demyelinating syndrome similar to multiple sclerosis seen in susceptible mice. The TMEV capsid peptide VP2(121–130) sensitizes H-2D(b+) target cells for killing by central-nervous-system-infiltrating lymphocytes (CNS-ILs) isolated from C57BL/6 mice infected intracranially. D(b):VP2(121–130) peptide tetramers were used to stain CD8(+) CNS-ILs, revealing that 50 to 63% of these cells bear receptors specific for VP2(121–130) presented in the context of D(b). No T cells bearing this specificity were found in the cervical lymph nodes or spleens of TMEV-infected mice. H-2(b) mice lacking CD4, class II, gamma interferon, or CD28 expression are susceptible to persistent virus infection but surprisingly still generate high frequencies of CD8(+), D(b):VP2(121–130)-specific T cells. However, CD4-negative mice generate a lower frequency of D(b):VP2(121–130)-specific T cells than do class II negative or normal H-2(b) animals. Resistant tumor necrosis factor alpha receptor I knockout mice also generate a high frequency of CD8(+) CNS-ILs specific for D(b):VP2(121–130). Furthermore, normally susceptible FVB mice that express a D(b) transgene generate D(b):VP2(121–130)-specific CD8(+) CNS-ILs at a frequency similar to that of C57BL/6 mice. These results demonstrate that VP2(121–130) presented in the context of D(b) is an immunodominant epitope in TMEV infection and that the frequency of the VP2(121–130)-specific CTLs appears to be independent of several key inflammatory mediators and genetic background but is regulated in part by the expression of CD4.